A microwave study of the hetero-chiral dimer of butan-2-ol - King, A; Howard, B (2001)
The first observation of a rotationally resolved spectrum for a dimeric complex of chiral molecules is reported. The complex in question is a hydrogen-bonded dimer of butan-2-ol and is shown to be hetero-chiral in composition. The rotational constants and components of the dipole moment agree well with the predictions of an ab initio study, the initial results of which are also reported. The ability of chiral species to form diastereoisomeric hetero- and homo-chiral complexes is thus given strong support. © 2001 Elsevier Science B.V.